vel non legi, vel saltuatim tantum: Megjegyzések Anna Maria van Schurman latin nyelvű költeményeihez - Nagyillés, János (Antikvitás & Reneszánsz, 2018)
The Latin poems by Anna Maria van Schurman, Dutch painter, engraver, poet, and scholar are not very well known. Their Christian author confessed in her Eukleria seu Meliores Partis Electio (Eucleria, or Choosing the Better Part) she had only read Greek and Latin authors who met the demands of serious Christian morals. Close lexical study of her Latin poems prove that she actually read some other Latin texts that were not suitable for her own high moral standards.